Telhado verde e telhado frio e suas contribuições para a redução da temperatura ambiente em construções na cidade de Cascavel no Oeste do estado do Paraná - Tonietto, Thayara Letícia (2021)
Since the industrial era, energy has played a fundamental role in our society, moving systems and equipment. As its usage increased, it has become pricier and insufficient. Thus, various and different ways of strategies have been developed so to minimize its use, not losing the offered quality, tough, mainly in building sector. Since the roof is one of the most important elements of constructions receiving solar radiation directly and nearly all day long, alternatives made to minimize those thermal loads are relevant, since they diminish the internal temperatures inside the buildings, consequently diminishing the energy consumption. For instance, some techniques such as green roofs and cold roofs in roof coverings have been more and more studied and applied in building industry. Thus, the present work aimed evaluating and comparing those two strategies, green roofs and reflexive roofs, whose focus was in the ambience comfort, by analyzing the 3 prototypes, which will be installed in the city of Cascavel, Paraná Sate. One of the prototypes is green, one made of fiber-cement tile and thermal white paint, one made of conventional fiber-cement tile with no treatment, which is a witness. We will evaluate the internal and external temperatures of the prototypes through sensors as well as their losses towards the ambience along day and night. Subsequently, the data will be inserted in the software Sisvar 5.6 for comparing the average among the treatments, with Tukey test at 5% of probability. The mean temperatures of the prototype of the cold and green roofs were equal and lower than the control prototype, whereas the moisture of the green roof obtained a more satisfactory result. Thus, due to the high costs of implementing a green roof, the cold roof is an option for rural buildings.